Characteristics of Relative Age Effects and Anthropometric Data in Japanese Recreational and Elite Male Junior Baseball Players - Yoichi Katsumata (Sports Medicine - Open, 2018)
Abstract Background The mechanisms underlying the relative age effect (RAE), a biased distribution of birth dates, in sport events have been investigated for more than two decades. The present study investigated the characteristics of the RAE in baseball and anthropometric data (height and weight) among recreational junior baseball players as well as elite players, using data extracted from national surveys. Methods Birth and anthropometric data were obtained from 4464 Japanese students as elementary school, junior high school, and high school players. Results Significant RAEs were noted in recreational junior high school and high school players, but not in elementary school players, and the effect size became larger with increasing grade (0.063 in elementary school players, 0.151 in junior high school players, and 0.227 in high school players). We also observed a significant RAE for elite elementary, junior high, and high school players. However, the effect size of elite players became smaller with increasing grade (0.563 in elementary school players, 0.358 in junior high school players, and 0.343 in high school players). Height and weight values were significantly larger in elite elementary and junior high school players than in recreational elementary and junior high school players, but height was almost the same between recreational and elite high school players. Conclusion The characteristics of RAEs differed between recreational and elite junior baseball players. Anthropometric data were also different, depending on birth data, and between recreational and elite baseball players in elementary and junior high school students.